The Role of Aloe vera and Centella asiatica to the Improvement of Skin Barrier Function in Indonesian Batik Workers - Damayanti; Menul Ayu Umborowati; Sylvia Anggraeni2; Cita Rosita Sigit Prakoeswa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The batik industry uses dyes and candles, that can disrupt the skin barrier function and may precipitate skin disease. Objective: To determine the role of Aloe vera and Centella asiatica to the improvement of the skin barrier function in Indonesian batik workersMethods: This was a double blind clinical trial of 30 Indonesian batik workers were divided into 2 group and given Aloe vera or Centella asiatica topical randomly was applied twice a day. Transepidermal water loss (TEWL) level, stratum corneum hydration level, and pH level, were examined using Cutometer dual MP-580. Result: Sensitivity (Sn) of new local compared with imported allergen extracts in this study was between 15.38%-84.61%, the highest point was house dust mite extract. Specificity (Sp) was ranged from 81.48%-93.75%, the highest rank was shrimp extract. Compared with IgE results, the Sn of new local and imported house dust mite extracts was good (85.7%; 92.9%). The Sp was good for egg white and cow’s milk new local extracts (86.4%; 84.4%). Conclusion: Aloe vera topical gave significant improvement on palm area of TEWL level (P=0.033; CI 95%), stratum corneum hydration (P=0.000; CI 95%), and pH level (P=0.004; CI 95%); while on dorsal hand area of stratum corneum hydration (P=0.002; CI 95%). Centella asiatica topical gave significant improvement on palm area of stratum corneum hydration (P=0.007; CI 95%); while on dorsal hand area of stratum corneum hydration (P=0.001; CI 95%) and pH level (P=0.17; CI 95%). No significant differences of Aloe vera compared to Centella asiatica in the improvement of skin barrier function.